2018
DOI: 10.3892/etm.2018.6985
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study in leg telangiectasias treatment with Nd:YAG laser and sclerotherapy

Abstract: Telangiectasias and reticular veins of the lower extremities are common lesions. Sclerotherapy is considered the gold standard for treatment. The aim of our prospective randomized study was to compare the efficacy and safety of hypertonic 20% saline/2% lignocaine (HS) versus polidocanol 0.5% (POL) versus long-pulsed neodymium:ytrium aluminium garnet (Nd:YAG) laser (LAS) treatments of leg telangiectasias in women, using each patient as her own control. We included in this study 285 women with primary leg telang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 15 publications
0
24
0
2
Order By: Relevance
“…269,270 Comparing sclerotherapy with transcutaneous laser (TCL), sclerotherapy has been shown to be as effective as 1064 nm Nd:YAG TCL, especially in treatment of reticular veins > 1 mm, but markedly less painful. 271,272 One RCT demonstrated statistically significant lower efficacy of sclerotherapy with POL compared with 1064 nm Nd:YAG in the treatment of telangiectasias < 1 mm (95% vs. 53%; p < .001), 268 whereas two other trials did not confirm these results and found no statistically significant difference in disappearance of veins with a diameter of 0.2 e 2.9 mm and no difference in patient satisfaction between sclerotherapy and Nd:YAG. 271,272 Sclerotherapy related adverse events have been described in detail in subsection 4.2.2.2.…”
Section: Class Level Referencesmentioning
confidence: 99%
“…269,270 Comparing sclerotherapy with transcutaneous laser (TCL), sclerotherapy has been shown to be as effective as 1064 nm Nd:YAG TCL, especially in treatment of reticular veins > 1 mm, but markedly less painful. 271,272 One RCT demonstrated statistically significant lower efficacy of sclerotherapy with POL compared with 1064 nm Nd:YAG in the treatment of telangiectasias < 1 mm (95% vs. 53%; p < .001), 268 whereas two other trials did not confirm these results and found no statistically significant difference in disappearance of veins with a diameter of 0.2 e 2.9 mm and no difference in patient satisfaction between sclerotherapy and Nd:YAG. 271,272 Sclerotherapy related adverse events have been described in detail in subsection 4.2.2.2.…”
Section: Class Level Referencesmentioning
confidence: 99%
“…205 In the same year, a randomized comparative study assessing hypertonic saline, polidocanol and Nd:YAG concluded that sclerotherapy remains the gold standard in vessels >1 mm, while Nd:YAG can have a role in smaller vessels. 206 Always in 2019, the feasibility of combining 532 and 808 nm multi-wavelength emissions for <1 mm vessels was demonstrated. 207…”
Section: Significant Recent Data Related To the Meeting Discussionmentioning
confidence: 99%
“…The main symptoms in moderate stages are heavy legs, tension in the lower limbs, varicose veins dilated, followed in severe stages by swelling of the lower limbs, skin changes, and the appearance of venous ulcer ( Lichota et al, 2019 ). A therapeutic option is represented by laser therapy, sclerotherapy, and venoactive drugs ( Ianosi et al, 2019 ). These venoactive drugs are a heterogeneous group of substances from plant or synthetic origin that modulate the venous tone, attenuates the blood rheology, improves micro- and macrocirculation, regulates capillary permeability, have anti-inflammatory effects by inhibiting leukocyte–endothelial interaction, and reduces the oxidative stress ( Salehi et al, 2020b ).…”
Section: Chalcones In Clinical Trialsmentioning
confidence: 99%